A multi-dimensional integrated approach to assess flood risks on a coastal city, induced by sea-level rise and storm tides. (8th January 2016) - Lilai, Xu; Yuanrong, He; Wei, Huang; shenghui, Cui
Abstract: Coastal cities are vulnerable to increasing flood risks caused by the combination of sea-level rise (SLR) and storm tides (STs), due to their low-lying topography and densely distributed assets. Faced with this challenge, comprehensive and integrated flood risk information is vital and fundamental for the planning, implementation and optimization of coastal risk adaptation and management. The goal of this study is to propose an integrated assessment approach to sea-level rise- and storm tide-induced flood risks on a coastal urban system by employing a wide range of indicators across ecological, physical and socio-economic dimensions. To demonstrate its applicability, a case study of Xiamen City, China was performed. The results show that this approach is applicable for assessing the specific flood risks on urban ecological, physical and socio-economic system, respectively. Under 4.75 ∼ 5.86 m extreme sea-level, 11 600 ∼ 17 100 ha land and 440 000 ∼ 720 000 population will be flooded in Xiamen City, with flood risks—measured by monetary—of 858 ∼ 1134 million, 4744 ∼ 10 590 million and 2537 ∼ 4175 million RMB of ecological, physical and economic systems, respectively. Coastal ecosystem will suffer flood risks on ecological services, mainly regulation service; and wetland is the dominant ecosystem that will be affected, which imply urgent needs to wetland conservation. Indirect risk on economy accounts for a large proportion of total risks, and should be given adequate weight in the decision-making process.